A construção da arqumentação na língua brasileira de sinais: divergência e convergência com a língua portuguesa - Sousa, Wilma Pastor de Andrade (2009)
With this research, our general objective is to make explicit how the argumentation construction in the Brazilian sign language (LIBRAS) is processed, based on a corpus comprising 12 video filmings, from which we selected four episodes to analysis. Ten deaf subjects took part in these, children and adolescents, regularly enrolled in the first series of elementary and secondary school in a certain public school of the state network in the city of Recife, PE, ranging from 04 to 14 years of age and an average time of five years of LIBRAS acquisition. We started out, so, from the hypotheses that the argumentation in LIBRAS happens in consonance with the acquisition of other discursive movements and it is built by means of strategies also based on non-verbal language with emphasis on proxemics and kinesics. The theoretical support to our investigation associates propositions of cognitive psychology and interactive linguistics, since both privilege dialogical and sociohistorical aspects as for the treatment of the language. The analysis pointed out the fact that the argumentation in LIBRAS appears in consonance with other discursive movements of resuming and topic switching argumentative activities frequently marked, par excellence, by the proxemics movement, besides by alterations in movement speed, body expression and facial extent and hand tension, used by LIBRAS speakers as strategies typical of this language during the argumentation, because of its space-visual nature. The results point out the fact that the argumentation emerges, in LIBRAS, just as it occurs in oral languages.